Simplified non-linear seismic analysis of infilled reinforced concrete frames. - Dolsek, Matjaz
The N2 method for simplified non-linear seismic analysis has been extended in order to make it applicable to infilled reinforced concrete frames. Compared to the simple basic variant of the N2 method, two important differences apply. A multi-linear idealization of the pushover curve, which takes into account the strength degradation which occurs after the infill fails, has to be made, and specific reduction factors, developed in a companion paper, have to be used for the determination of inelastic spectra. It is shown that the N2 method can also be used for the determination of approximate summarized IDA curves. The proposed method was applied to two test buildings. The results were compared with the results obtained by non-linear dynamic analyses for three sets of ground motions, and a reasonable accuracy was demonstrated. A similar extension of the N2 method can be made to any structural system, provided that an appropriate specific R-u-T relation is available.
Keywords: Simplified non-linear analysis; Inelastic spectrum; Infilled RC frame; N2 method; Incremental dynamic analysis